The Influence of Product Quality, Product Innovation, and Brand Image on Purchase Decisions - Angelina Anggraini; K. Emi Trimiati (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
Consumer purchase decisions are influenced by various factors, including product quality, product innovation, and brand image. In the increasingly competitive fashion industry, understanding the determinants of purchase decisions is essential for maintaining business performance and achieving sustainable growth. This study aims to examine the effects of product quality, product innovation, and brand image on consumers’ purchase decisions toward Jims Honey Jenira products. A quantitative approach was employed using a survey method. Data were collected from 100 consumers of Jims Honey Jenira through structured questionnaires using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS. Prior to hypothesis testing, validity, normality, multicollinearity, and heteroscedasticity tests were conducted to ensure the suitability of the regression model. The results indicate that product quality, product innovation, and brand image each have a positive and significant effect on purchase decisions. Simultaneously, the three variables significantly influence purchase decisions, as demonstrated by the F-test results. Among the independent variables, product innovation exhibits the strongest contribution to purchase decisions, indicating that consumers place considerable importance on novelty and product development in the fashion sector. Furthermore, the coefficient of determination (R²) of 0.854 indicates that 85.4% of the variation in purchase decisions can be explained by product quality, product innovation, and brand image. The findings suggest that fashion businesses should focus on improving product quality, continuously introducing innovations, and strengthening brand image to enhance consumer purchase decisions and sustain competitive advantage.